Internal reference genes with the potential for normalizing quantitative PCR results for oral fluid specimens. (4th December 2022) - Cheng, Ting-Yu; Zimmerman, Jeffrey J.; Giménez-Lirola, Luis G.
Abstract: In basic research, testing of oral fluid specimens by real-time quantitative polymerase chain reaction (qPCR) has been used to evaluate changes in gene expression levels following experimental treatments. In diagnostic medicine, qPCR has been used to detect DNA/RNA transcripts indicative of bacterial or viral infections. Normalization of qPCR using endogenous and exogenous reference genes is a well-established strategy for ensuring result comparability by controlling sample-to-sample variation introduced during sampling, storage, and qPCR testing. In this review, the majority of recent publications in human ( n = 136) and veterinary ( n = 179) medicine did not describe the use of internal reference genes in qPCRs for oral fluid specimens (52.9% animal studies; 57.0% human studies). However, the use of endogenous reference genes has not been fully explored or validated for oral fluid specimens. The lack of valid internal reference genes inherent to the oral fluid matrix will continue to hamper the reliability, reproducibility, and generalizability of oral fluid qPCR assays until this issue is addressed.